A Sharp Jump in Photocatalytic Activity of Elemental Sulfur for Dye Degradation in Alkaline Solution. (14th July 2020) - Peyman, Vahideh Alvandi; Azizian, Saeid
Abstract: Elemental sulfur is a low‐cost and abundant substance as one of the largest by‐products of the oil industry which was widely used in many industrial activities. Cyclo‐octasulfur (S8 ) is one of the sulfur allotropes that is a very stable substance in standard conditions. In this study, we report a low‐cost and fast method for the degradation of methyl violet in water under visible light and also sunlight by using elemental sulfur (S8 ). The results show that sulfur is a good photocatalyst which operates under visible light and can be utilized for degradation of methyl violet. The photocatalytic degradation of methyl violet in acidic, neutral, and alkaline media was investigated, and it was found that the photocatalytic efficiency increases dramatically in alkaline solution. The effects of the initial concentration of the dye, photocatalyst dosage, solution pH, and photocatalyst reusability were investigated. The kinetics of the reaction were studied in detail, and the photocatalytic rate equation was presented. Abstract : Elemental sulfur, an available and low cost material, is an efficient photocatalyst in alkaline solution for dye degradation.